The leader region of Laminin B1 mRNA confers cap-independent translation - Petz, Michaela (Oxford University Press, 2007)
Translation initiation of eukaryotic mRNAs generally occurs by cap-dependent ribosome scanning. However, certain mRNAs contain internal ribosome entry sites (IRES) allowing cap-independent translation. Several of these IRES-competent transcripts and their corresponding proteins are involved in tumourigenesis. This study focused on IRES-driven translation control during the epithelial to mesenchymal transition (EMT) of hepatocytes that reflects crucial aspects of carcinoma progression. Expression profiling of EMT revealed Laminin B1 (LamB1) to be translationally upregulated. The 5′-untranslated region (UTR) of LamB1 was potent to direct IRES-dependent mRNA utilization of a bicistronic reporter construct. Stringent assays for cryptic promoter and splice sites showed no aberrantly expressed transcripts, suggesting that the reporter activity provided by the leader region of LamB1 mRNA exclusively depends on IRES. In accordance, LamB1 expression increased upon negative interference with cap-dependent translation by expression of human rhinovirus 2A protease or heat shock of cells. Finally, the enhanced expression of LamB1 during EMT correlated with an elevated IRES activity. Together, these data provide first evidence that the 5′-UTR of LamB1 contains a bona fide IRES that directs translational upregulation of LamB1 during stress conditions and neoplastic progression of hepatocytes.